2021
DOI: 10.1016/j.ijscr.2021.106170
|View full text |Cite
|
Sign up to set email alerts
|

A case report of gallbladder cancer and pancreas cystic neoplasm associated with pancreaticobiliary maljunction

Abstract: Introduction and importance Pancreaticobiliary maljunction (PBM) is a rare congenital anomaly that is frequently associated with carcinoma of the biliary tract. However, there is still no clear evidence that PBM is associated with pancreatic tumors. Here we describe a case of gallbladder cancer and intraductal papillary mucinous neoplasm (IPMN) that is associated with PBM. Case presentation A 72-year-old man underwent a cholecystectomy with hepatectomy (S4a + S5) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Unlike biliary tract cancer, the relationship between PBM and pancreatic cancer remains unclear. Recently, Sato K et al published a case report containing literature review of PBM and pancreatic cancer [ 7 ]. In this report, pancreatic cancer associated with congenital biliary dilatation revealed that biliary tract cancer preceded the pancreatic cancer in all metachronous multiple cancer cases.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike biliary tract cancer, the relationship between PBM and pancreatic cancer remains unclear. Recently, Sato K et al published a case report containing literature review of PBM and pancreatic cancer [ 7 ]. In this report, pancreatic cancer associated with congenital biliary dilatation revealed that biliary tract cancer preceded the pancreatic cancer in all metachronous multiple cancer cases.…”
Section: Discussionmentioning
confidence: 99%